EVALUATION OF THE POTENTIAL CYTOTOXICITY OF RUTHENIUM COMPLEX II AGAINST U-373 GLIOBLASTOMA CELLS - J. SAADH, MOHAMED; AL-WAHISH, MOHAMMED A. (International Journal of Applied Pharmaceutics, 2023)
Objective: The potential of ruthenium complexes as anticancer agents has gained significant attention in the scientific community. The aim of this study was to investigate the effect of dithiocyanato-N-bis[8(diphenylphosphino)quinoline]ruthenium (II), [Ru(N-P)2(NCS)2] on the glioblastoma U-373 tumor cells and apoptosis. Methods: Ru(N-P)2(NCS)2] was synthesized and characterized using FTIR, and X-ray crystallography. The cytotoxic effects of [Ru(N-P)2(NCS)2] on glioblastoma U-373 tumor cells were evaluated using both the trypan blue assay and the activity of caspase-3 to detect apoptosis. A DPPH scavenging assay was used to evaluate the antioxidant activity. Results: The [Ru(N-P)2(NCS)2] complex effectively inhibited the glioblastoma U-373 tumor cells with an IC50 of 23 µg/ml. Similar to the majority of chemotherapeutic agents that kill via the intrinsic pathway, [Ru(N-P)2(NCS)2] induces apoptosis, which was confirmed by the activation of caspase-3, and these effects were dose-dependent. Ruthenium has antioxidant properties, so ruthenium Complex II exhibits lower toxicity towards normal cells while effectively targeting and eliminating cancer cells. Conclusion: [Ru(N-P)2(NCS)2] is considered promising for researchers investigating putative biological activities, particularly antitumor and immune-related activity.